The BRICS's Economic Growth Performance before and after the International Financial Crisis. Issue 4 (1st October 2016) - Nassif, André; Feijo, Carmem; Araújo, Eliane
Abstract: The aim of this paper is to shed some light on the issue of why some BRICS countries are doing much better than others after the international financial crisis. Although these economies share some common economic historical ground, and collectively had been performing much better than the world average in the last decades, their room to maneuver to administrate short-term economic policy to sustain growth in the context of world recession is not similar. Our main assumption is that their different performances can be explained by the degree of their external vulnerabilities, which basically depend on how cautious they were to embrace the liberal policy orientations that became dominant in the 1980s and 1990s with the so-called new macroeconomic consensus.